Effect of Oral Pregabalin Premedication on Post-Operative Pain in Laparoscopic Gastric Bypass Surgery - Alimian, Mahzad (Kowsar, 2012)
BACKGROUND: Post-operative pain and the administration of opioids to relieve it, is considered to be one of the important issues in surgery wards. This issue is even more significant in obese patients, because of the side effects of opioids. Pregabalin is an analog of gamma aminobutyric acid (GABA) which can be effective in dealing with post-operative pain. OBJECTIVES: This study will consider the effect of oral pregabalin in relieving the pain of obese patients after gastric bypass surgery. PATIENTS AND METHODS: In a double blind clinical trial, 60 candidates for laparoscopic gastric bypass surgery were enrolled in the study through convenience and non-random sequential sampling, into two groups; pregabalin group and control group. Inclusion criteria consisted of: morbid obesity with a body mass index (BMI) > 35, age 18–50, American Society of Anesthesiologists (ASA) status I or II, and willingness to take part in the study. Patients in the pregabalin group received 300 mg of oral pregabalin on the morning of the surgery. Post-operative pain was controlled by the patient-controlled intravenous analgesia (PCIA) method, an AutoMed infusion pump containing 20 mg of morphine and normal saline (total volume 100 cc) was administered to all patients after surgery. Patients’ level of pain were compared by considering their pain intensity on a visual analog scale (VAS), and the occurrence of nausea/vomiting from recovery, until 24 hours after surgery. RESULTS: A total of 60 patients were compared; 30 patients in each of the pregabalin and control groups. Both groups were similar in age and sex distribution. Mean pain intensity levels during the whole follow up were lower in the pregabalin group than in the control group, up to a maximum of 24 hours after the operation (P < 0.001). Incidence of nausea/vomiting was greater in the control group than in the pregabalin group (P < 0.001). CONCLUSIONS: The findings of this study indicate that oral pregabalin (300 mg dose) can alleviate patients’ pain and nausea/vomiting and notably reduce adverse effects.